2016
DOI: 10.1080/09515089.2016.1150448
|View full text |Cite
|
Sign up to set email alerts
|

Outsourcing the deep self: Deep self discordance does not explain away intuitions in manipulation arguments

Abstract: Manipulation arguments have figured prominently in recent debates about incompatibilism about moral responsibility, with compatibilists of various stripes seeing these arguments as particularly challenging. 1 In its basic form, a manipulation argument for incompatibilism tries to establish that there is a case of manipulation such that: UNDERMINING: It undermines the moral responsibility of the manipulated agent. EQUIVALENCE: It is not relevantly different from any other form of deterministic causal influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…A first group set of studies tries to directly address the compatibility question, by investigating whether people think that an agent in a deterministic universe can be free and morally responsible. A second group indirectly addresses the question by studying whether people share the intuitions that serve as premise to philosophical arguments for and against the compatibility of free will with determinism, such as Frankfurt-style cases (Cova, 2014(Cova, , 2017Miller & Feltz, 2011) or Manipulation arguments (Björnsson, 2016;Cova, forthcoming;Feltz, 2013;Sripada, 2012). In this chapter, I focus on studies that try to directly address the compatibility question.…”
Section: Two Main Positions: Natural Compatibilism Vs Natural Incompatibilismmentioning
confidence: 99%
“…A first group set of studies tries to directly address the compatibility question, by investigating whether people think that an agent in a deterministic universe can be free and morally responsible. A second group indirectly addresses the question by studying whether people share the intuitions that serve as premise to philosophical arguments for and against the compatibility of free will with determinism, such as Frankfurt-style cases (Cova, 2014(Cova, , 2017Miller & Feltz, 2011) or Manipulation arguments (Björnsson, 2016;Cova, forthcoming;Feltz, 2013;Sripada, 2012). In this chapter, I focus on studies that try to directly address the compatibility question.…”
Section: Two Main Positions: Natural Compatibilism Vs Natural Incompatibilismmentioning
confidence: 99%
“…In considering the effects of determinism on consciousness, the most straightforward hypothesis is that determinism affects attributions of free will which, in turn, affect attributions of consciousness. Numerous studies have shown how determinism affects attributions of free will (see, e.g., Nahmias et al, 2007 ); however, there is considerable evidence that determinism affects related areas of agency attribution, such as attributions of decisions or deliberation ( Björnsson, 2014 ; Rose & Nichols, 2013 ) as well as attributions of an agent’s being the source of her own action ( Björnsson, 2016 ). There is also weak evidence suggesting that attributions of belief are affected ( Murray & Nahmias, 2014 ; for reasons to be skeptical, see Björnsson, 2014 ).…”
Section: Studymentioning
confidence: 99%
“…Chandra Sripada (2012) takes studies of his to suggest that people take manipulation to undermine responsibility because they take it to undermine certain compatibilist conditions. However, further studies undermine Sripada's interpretation of the data and provide contrary evidence in line with the current proposal (Björnsson 2016 substandard quality of will of the agent. In doing so, they prompt us to see his quality of will as, at best, a mere dependent variable.…”
Section: Figure 1 Explanatory Model (Grey Area) With Background Condmentioning
confidence: 55%